2021
DOI: 10.1177/2473974x211052857
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Identification of Normal Parathyroid Glands

Abstract: Ultrasound has become indispensable for identification of thyroid and parathyroid pathology, but normal parathyroid glands have historically been considered too subtle to accurately detect. Inability to identify and protect parathyroid glands can result in hypoparathyroidism and hypocalcemia during thyroidectomy surgery as well as misinterpretation of central neck structures in the postoperative neck. Advances in ultrasound resolution have opened the door to novel applications for this technology. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…In two cases of normal PTGs with focal intraglandular hypoechogenicity, the residual hyperechoic area consistently showed the same homogeneous marked hyperechogenicity as the other typical normal PTGs. A recent study [ 12 ] reported that all normal PTGs showed homogeneous hyperechogenicity in six cases. However, in their study, the echogenicity of normal PTGs was not clearly evaluated compared to that of the normal thyroid gland.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In two cases of normal PTGs with focal intraglandular hypoechogenicity, the residual hyperechoic area consistently showed the same homogeneous marked hyperechogenicity as the other typical normal PTGs. A recent study [ 12 ] reported that all normal PTGs showed homogeneous hyperechogenicity in six cases. However, in their study, the echogenicity of normal PTGs was not clearly evaluated compared to that of the normal thyroid gland.…”
Section: Discussionmentioning
confidence: 99%
“…Cohen et al [12] also reported that the normal PTGs confirmed by tissue washout parathyroid hormone (PTH) or autofluorescence showed homogeneously hyperechoic US feature. To the best of our knowledge, only one study [12] reported US features of six cases of normal parathyroid glands confirmed by biochemical method. However, the detailed US features of normal PTGs identified by histopathological or biochemical methods remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal parathyroid glands are difficult to identify on US, owing to their small size and subtle US characteristics [ 36 ]. A recent investigation suggests that normal parathyroid glands can in fact sometimes be seen on US as small oval homogeneously hyperechoic structures ([ 37 ]; Fig. 5 a).…”
Section: Parathyroid Ultrasonographymentioning
confidence: 99%
“…US is an essential primary tool for the evaluation and localization of parathyroid lesions and is advantageous for localization of small normal PTGs because of its high resolution and feasible application. However, normal PTGs are rarely detected on US ( 4 5 6 7 ), and the US features of normal PTGs have not yet been established ( 6 8 9 ).…”
Section: Introductionmentioning
confidence: 99%